Innovative strategies for carbon dioxide retention in the curing process of precast plain mass concrete elements - Scurtu Ioan Nicolae; Mircea Călin Grigore Radu; Mircea Andreea Terezia; Toader Tudor-Panfil; Lăzărescu Adrian Victor; Hegyi Andreea (MATEC Web of Conferences, 2025)
Research on carbon dioxide capture and storage technologies through accelerated carbonation of cement-based materials, is gaining increasing interest in the construction sector. This study aims to present the capacity of carbon dioxide (CO₂) capture and storage, as well as the effects of the carbonation on the physical and mechanical behaviour of precast vibrated plain mass concrete elements. The analysis includes various methods to enhance the efficiency of the carbonation process and accelerate it, emphasizing the importance of optimizing reaction conditions. The research findings suggest that the carbonation process can significantly improve the mechanical performance of these precast elements, making them more durable and efficient. Critical parameters, such as water content, sample size, environmental pressure, and temperature, considerably influence the efficiency of carbon dioxide capture. Furthermore, the study proposes directions for implementing rapid CO2 sequestration technologies, highlighting their potential to contribute to decarbonization. The research aims to open new perspectives for the use of plain mass concrete precast elements while facilitating the exploration of innovative solutions in the context of sustainable development. In conclusion, the carbonation of precast concrete elements proves to be a promising approach in the fight against climate change, with direct applications in the construction industry and beyond.